GENERALIZATION OF EUROPEAN EXPERIENCE IN THE FORMATION OF MODERN SOCIAL HOUSING - Seleshok, Ivan (Theory and practice of design, 2025)
Purpose. The purpose of this article is to summarize the European experience in the formation of modern social housing and to identify architectural and planning principles that can be adapted to the Ukrainian context of post-war reconstruction. The research aims to determine the typological, morphological, and functional-spatial characteristics of social housing that correspond to the principles of sustainable development and ensure social integration within the urban environment. Methodology. The study is based on a systemic and comparative-analytical approach that combines typological, morphological, and graphic-analytical methods. The research relies on the analysis of implemented examples of social housing in European countries such as Sweden, Denmark, the Netherlands, Germany, and Switzerland. Official reports of Housing Europe, UNECE, and Cedos were used as the analytical foundation. The methodological framework also includes visual analysis and comparative mapping of housing typologies to reveal patterns of planning organization. Results. It has been established that social housing in European countries is characterized by a mixed typology of development, integration with public spaces, and a balance between density and comfort. The architecture of such complexes demonstrates that social housing is not synonymous with minimal standards or poor quality, but rather corresponds to the level of commercial housing of the “comfort” class. The projects analyzed feature inclusive public areas, energy-efficient technologies, and environmentally friendly materials. The study highlights the importance of sustainable design, multifunctionality, and social diversity as core principles of contemporary housing development. Scientific novelty. For the first time, the architectural and planning parameters of social housing in European countries have been systematized from the perspective of sustainable development and potential adaptation to Ukrainian realities. The article clarifies the concept of sustainable-type social housing as a spatial and social system focused on flexibility, inclusiveness, and ecological balance. Practical relevance. The research results can be applied in the development of guidelines and state standards for designing social housing in Ukraine, particularly within the framework of post-war reconstruction. The proposed principles provide a methodological basis for creating sustainable, energy-efficient, and socially integrated housing environments that contribute to the formation of resilient local communities.